A Computational Study of the Gas-Solid Suspension Flow through a Supersonic Nozzle - Sun, Jian G.; Kim, Heuy D.; Park, Jin O.; Jin, Ying Z. (Scientific Research, 2012)
The present study focuses on numerical simulation of the gas-solid suspension flow in a supersonic nozzle. The Euler- Lagrange approach using a Discrete Phase Model (DPM) has been used to solve the compressible Navier-Stokes equations. A fully implicit finite volume scheme has been employed to discretize the governing equations. Based upon the present CFD results, the particle loading effect on gas-solid suspension flow was investigated. The results show that the presence of particles has a big influence on the gas phase behavior. The structure of shock train, the separation point, and the vortex of the backflow are all related to particle loading. As the particle loading increases the flow characteristics behave differently such as 1) the strength of shock train decreases, 2) the separation point moves toward the nozzle exit, 3) the number and strength of vortex increase, 4) the strength of first shock also increases while the other pseudo shocks decreases. The change of gas flow behavior in turn affects the particle distribution. The particles are concentrated at the shear layers separated from the upper wall surface.
Keywords: Shock Wave; Internal Flow; Flow Choking; Supersonic Nozzle; Gas-Solid Suspension Flow